Advances in the Study of the Ubiquitin-Editing Enzyme A20 - Bai, Wenya; Huo, Siying; Li, Junjie; Shao, Jianlin (Frontiers in Pharmacology, 2022)
Ubiquitin modification is a common post-translational protein modification and an important mechanism whereby the body regulates protein levels and functions. As a common enzyme associated with ubiquitin modification, the ubiquitin-editing enzyme A20 may be closely associated with the development of numerous pathological processes through its different structural domains. The aim of this paper is to provide an overview of the following: advances in ubiquitination research, ubiquitin-editing function of A20, and the relationships between A20 and immune inflammatory responses, apoptosis, pyroptosis, and autophagy.